Perlindungan Hukum Terhadap Pejalan Kaki Yang Menjadi Korban Penyalahgunaan Trotoar di Indonesia - Syifa Nurfajriana; Zainab Cahya Rosuli; Mulyadi M (Madani: Jurnal Ilmiah Multidisiplin, 2023)
In Indonesia, the government has facilitated the community by providing sidewalks for pedestrians. The sidewalk is one of the facilities for pedestrians which is located parallel to the traffic lane but has elevation that is higher than the surface of the road pavement and there is a layer on the road. In the use of sidewalks, the function of sidewalks in Indonesia is to provide safety and comfort for pedestrians when using the road. But unfortunately in reality, the use of sidewalks is often misused such as motorbike taxis, motorbike tricycles, motorbike carts, selling fruits/vegetables/clothing on cars and others who use sidewalk land as their place of business. The purpose of this research is to find out regulations related to the use of sidewalks in Indonesia, and legal protection for pedestrians who are victims of sidewalk abuse in Indonesia, especially DKI Jakarta. This research uses normative juridical or statutory approach. Based onLaw Number 22 of 2009 Concerning Road Traffic and Transportation in Article 45 paragraph (1) letter a which explains that sidewalks are one of the supporting facilities for the implementation of traffic and road transportation provided by the local government and there are sanctions for those who violate them .